(untitled) (Management and Connections Journal, 2021)
This article proposes to evaluate the national scientific production about transparency in public management, having as a starting point the publication of the LRF, covering 19 years (2000-2018) of academic production. 63 studies were reviewed, found in the Capes and Scielo databases, to address two questions: What forms of public management transparency identified in the literature? What results has the literature attributed to the transparency of public management? It is concluded that national studies on the subject of public transparency have emerged especially since the publication of the LAI and focus on empirical research with emphasis on the municipal level. Regarding the forms and results of transparency, the studies concentrate their efforts on addressing the administrative, budgetary, accountability and performance aspects, leaving aside the study of political aspects, managerial decision making, participation and, societal satisfaction.